1992
DOI: 10.2172/5588394
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on TFTR supershot plasmas

Abstract: This report was prepared as an account of work sponsored by an agency of the United , States Government.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1995
1995
1997
1997

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Since minimizing the hydrogenic influx can dramatically increase the plasma performance 4,5 it is clearly important to identify its dependence on plasma parameters. A dedicated experimental investigation of the parametric dependence of F 1 on plasma parameters would have required prohibitively high tritium usage, and so a study was undertaken of discharges in the existing database.…”
Section: Scaling Of Neutron Rate With Plasma Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Since minimizing the hydrogenic influx can dramatically increase the plasma performance 4,5 it is clearly important to identify its dependence on plasma parameters. A dedicated experimental investigation of the parametric dependence of F 1 on plasma parameters would have required prohibitively high tritium usage, and so a study was undertaken of discharges in the existing database.…”
Section: Scaling Of Neutron Rate With Plasma Parametersmentioning
confidence: 99%
“…The TFTR plasma boundary is defined by an inner toroidal belt limiter composed of 22 m 2 of carbon tiles. The deuterium influx from the limiter was minimized by ohmic conditioning discharges 4 and in some cases by lithium pellet injection. 5 However, despite the substantial reductions achieved, recycling from the limiter remained a major fueling source for the plasma (typically, there is no gas feed after the initiation of the discharge).…”
mentioning
confidence: 99%
“…The majority of experiments with D-T discharges in TFTR have been carried out in the "supershot" mode of plasma operation. The enhanced energy confinement, peaked density profiles and high fusion reactivity that characterize supershots are known to depend sensitively on the surface condition of the TFTR carbon inner limiter [ 6 ] . Moreover, it has been demonstrated that, in D-only supershots, energy confinement can be improved by depositing lithium (Li) onto the limiter [7,8,9,10].…”
mentioning
confidence: 99%
“…Although all the mechanisms by which Li conditioning contributes to plasma performance are not understood, reduced particle (mostly carbon and deuterium) influx from the limiter during NBI appears to play an important role in determining energy confinement in TFTR supershots [6,18]. In this regard, a clear result of Li conditioning can be seen on the edge electron density.…”
mentioning
confidence: 99%